PEMBELAJARAN DARING PADA MATA PELAJARAN PRODUKTIF (Studi Kasus Praktik Simkomdig OTKP SMK Negeri 3 Surakarta) - Annisa Nurul Firdhaus; Tri Murwaningsih; Patni Ninghardjanti (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2022)
The purpose of this research was to determine the implementation of e-learning in Simkomdig subject at OTKP SMKN 3 Surakarta. This study uses a qualitative method with a case study approach. Sources of data obtained from informants, places and occurrence, as well as documents and archives. The sampling technique used is purposive sampling and snowball sampling. Data collection techniques were carried out by interview, observation, and document analysis. Test the validity of the data using source triangulation and method triangulation. The data analysis technique uses an interactive analysis model. The implementation of online learning at Simkomdig OTKP SMKN 3 Surakarta consists of planning learning tools, preparing learning media and information technology that supports online learning. Conducted through the Google Classroom application, SMK3 e-learning, and Whatsapp causing the Simkomdig practicum material to be less than optimal. The online assessment is only taken from the time of collection of assignments and accuracy in answering. The obstacles found were differences in students' understanding abilities, limitations of electronic devices, unstable internet connections, lack of skills to operate electronic media optimally, and lack of learning supervision. Solutions to overcome obstacles in Simkomdig's online learning are carried out by selecting the right learning media, providing internet quota assistance and computer labs, training teachers on online applications, and further coordinating with parents or guardians of students.